Large exchange bias in Cr substituted Fe3O4 nanoparticles with FeO subdomains. Issue 37 (14th September 2021) - Bulbucan, Claudiu; Preger, Calle; Kostanyan, Aram; Jensen, Kirsten M. Ø.; Kokkonen, Esko; Piamonteze, Cinthia; Messing, Maria E.; Westerström, Rasmus
Abstract : Here we present a structural and magnetic characterization of a novel bimagnetic nanoparticle composed of a 40 nm Cr-substituted magnetite phase with 4 nm FeO subdomains exhibiting large exchange bias. Abstract : Tuning the anisotropy through exchange bias in bimagnetic nanoparticles is an active research strategy for enhancing and tailoring the magnetic properties for a wide range of applications. Here we present a structural and magnetic characterization of unique FeCr-oxide nanoparticles generated from seed material with a Fe : Cr ratio of 4.71 : 1 using a physical aerosol method based on spark ablation. The nanoparticles have a novel bimagnetic structure composed of a 40 nm ferrimagnetic Cr-substituted Fe3 O4 structure with 4 nm antiferromagnetic Fe x O subdomains. Cooling in an applied magnetic field across the Néel temperature of the Fe x O subdomains results in a significant shift in the hysteresis, demonstrating the presence of a large exchange bias. The observed shift of μ 0 H E = 460 mT is among the largest values reported for Fe x O–Fe3 O4 -based nanoparticles and is attributed to the large antiferromagnetic-ferrimagnetic interface area provided by the subdomains.